Analysis Of Food Ordering Agreement Through Application Of Online Transportation System In Islamic Economic Overview - Fajarillah Sitohang, Sahala; Marliyah, Marliyah; Batubara, Maryam (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research analyzes food ordering contracts via online transportation applications from an Islamic economic perspective. It was found that there are various electronic contracts that influence society, including the perception that booking contracts can be considered haram or contain gharar, affecting beliefs and the online transportation ecosystem. This research methodology is descriptive qualitative with primary data sources from interviews and secondary sources from books and papers. Data collection techniques include observation, interviews and documentation. The research results show that in Go-Food services by PT Go-Jek there are ijarah, wakalah, sale and purchase and musyarakah contracts. Ijarah contracts occur in service transactions, wakalah contracts when consumers represent purchases, sale and purchase contracts when drivers buy food, and musyarakah contracts in collaboration between PT Go-Jek and drivers. In addition, analysis of OVO top-up transactions shows that it is compatible with the Sarf contract, although a small number of users still consider it a Qardh contract due to the lack of socialization regarding the type of contract in OVO transactions